2019
DOI: 10.4081/pb.2019.7441
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of Six Corn Varieties (Zea mays L.) to Sitophilus zeamais Motschulsky (Coleoptera: Curculionidae)

Abstract: Agricultural produce is commonly stored in warehouses after the harvest period, before being utilized and fulfilling the crop stock. However, crop threats are not only present during cultivation and harvest, but crops can also be infected during storage, which leads to agricultural loss. This research aimed to observe the resistance level of corn varieties of Bisma, Bisi 18, Bisi 19, Pioneer 21, Pioneer 29, and Pertiwi 3 to the Sitophilus zeamaispest of stored product insects. This resistance was based on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
1
0
1
Order By: Relevance
“…La susceptibilidad del grano también se debe al aumento de almidón y proteínas (Nwosu et al, 2016). Además, Astuti et al (2019) observaron en diferentes híbridos de maíz la repelencia sobre S. zeamais debido al contenido alto de fibra, ácidos fenólicos e inhibición de la tripsina.…”
Section: Resultados Y Discusiónunclassified
“…La susceptibilidad del grano también se debe al aumento de almidón y proteínas (Nwosu et al, 2016). Además, Astuti et al (2019) observaron en diferentes híbridos de maíz la repelencia sobre S. zeamais debido al contenido alto de fibra, ácidos fenólicos e inhibición de la tripsina.…”
Section: Resultados Y Discusiónunclassified
“…In addition, according to Ngom et al (2020) variety-resistant maize is distinguished by high levels of amylose and moisture content, as well as high grain hardness; increasing amylose content might damage insect reproduction by interfering with digestion mechanisms (antibiosis mechanisms). It has also been demonstrated that resistant types had reduced grain damage and weight loss, which could be attributable to antixenosis resistance mechanisms that prevent the insect from laying eggs and feeding (Astuti et al, 2019). Several biochemical properties have been described to have an effect on maize resistance to S. zamias, and maize breeders have been successful in developing varieties with resistance to the maize weevil, but it is difficult to say that these efforts have reached their intended heights since some improved varieties of maize are broken down by the weevil under storage conditions (Nwosu, 2018).…”
Section: The Index Of Susceptibilitymentioning
confidence: 99%